Food's Ceramic Pot Source of Cadmium's Intoxication the Body Human - L. R. Babchuk (Фізика і хімія твердого тіла, 2018)
Heavy metal cadmium is classified to the World Health Organization to the most hazardous substances for human health. The aim is to study the food pottery as an object that can be a source of cadmium in the human body. The various kinds of food ceramic products, which may contain pigments based on cadmium compounds, are considered. It was found that the cadmium sulfide can be an integral part of underglaze or onglaze ceramic paints, glazes, ceramic mass and a chandelier. The most intense release of cadmium comes with glaze and paint ceramic mass and carries the greatest risk in respect of this heavy metal pollution of the human body. Process cadmium poisoning human body compounds can last for years, cadmium tends to accumulate in the body for a long time. Therefore, the use of externally beautiful, but the harmful chemical composition, color of ceramic tableware harmful to human health. Key words: ceramic tableware, heavy metal cadmium, cadmium sulfide, ceramic colors, glazes, chandelier.